AB0442 Regional Patterns of Tocilizumab Use, Efficacy, and Safety in Patients with Rheumatoid Arthritis: Interim Results from a Multinational Observational Study. (9th June 2015) - Haraoui, B.; Casado, G.; Theander, E.; Czirják, L.; Taylor, A.; Mikes, E.; Reiss, W.; Caporali, R.
Abstract : Background: Tocilizumab (TCZ) is an anti–interleukin-6 receptor antibody indicated for the treatment of patients with rheumatoid arthritis (RA). It can be prescribed either as monotherapy or in combination with disease-modifying antirheumatic drugs (DMARDs). ACT-UP is an umbrella project incorporating data from several prospective, international, observational, postmarketing studies investigating TCZ use in patients with RA in routine care. Objectives: To investigate regional patterns of intravenous (IV) TCZ use, efficacy, and safety over 6 months of treatment in ACT-UP. Methods: Adults with moderate to severe RA who started IV TCZ within 8 weeks of enrollment were observed in clinical practice for 6 months. There were no specified dosing regimens (concomitant RA treatments were permitted) and no interventional procedures, clinic visits, or laboratory analyses outside routine practice. Regional differences were investigated across studies performed in different countries. Results: Of 1257 patients who received their first TCZ dose by January 31, 2014, 679 were from Europe, 198 from Canada, 184 from Israel, 115 from South America, 44 from Indonesia, and 37 from Australia. The mean age of patients was 55.0 years and ranged from 44.1 years in Indonesia to 59.3 years in Australia. While 81% of all patients were female, the percentage of female patients was lowest in Australia (57%) and highest in Central America (92%). Patterns of TCZ use by region are shown in the table . Overall, 22 of 431 patients (5.1%) receiving monotherapy switched to combination therapy during the study. The proportion of patients remaining on TCZ after 6 months was 82.7% (95% confidence interval: 80.5%, 84.8%). Mean concomitant MTX dose including baseline and during the study ranged from 10.0 to 18.8 mg/week across regions. Corticosteroids (CSs) were taken by 43.8% of patients at baseline, and mean (range) CS dose was 8.3 (5.0-10.3) mg/day, with some fluctuations among regions. Of 466 patients who had an assessment of disease activity at 6 months, 92.7% reported EULAR good or moderate responses, with similar response rates across all regions (Table ). Overall, 650/1257 (52%) patients reported adverse events (AEs), and 102/1257 (8%) reported serious AEs (SAEs). Events occurring under the system organ class of infections and infestations were the most common AEs (19.5%) and SAEs (2.0%) reported. Conclusions: At 6 months, there was high persistence of TCZ use that was greater than 90% in some regions of the world. Although there were some regional differences in baseline characteristics and patterns of TCZ use, the effectiveness of TCZ at 6 months was high across regions. Over 6 months of use in clinical settings, the reported safety of TCZ was consistent with the known safety profile. Disclosure of Interest: B. Haraoui Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB, G. Casado: None declared, E. Theander Speakers bureau: Roche, L. Czirják: None declared, A. Taylor Consultant for: Roche, Celgene, AbbVie, Pfizer, UCB, E. Mikes Employee of: Roche, W. Reiss Employee of: Roche, R. Caporali: None declared